TRILOGI PEMBEBASAN ASGHAR ALI ENGINEER: Tafsir Anti Kemapanan atas Ketidakadilan - Fahmi Riady (Pascasarjana UIN ANTASARI Banjarmasin, 2008)
The liberation theology is a theology which puts great ernphasis on fieedom, equality and distributive justice and strongly condemns exploitation of rnan by man, opprcssion and pcrsccution. l'he main character ol'this thcology is its conccrn to thc mustadh'afun (the weak people). Suclr tlrc ology didn't want the status quo rvhich protect the rich people. It's anti-status quo either in religoLrs field or politic one. Such theology play the imporlant role in caring tbr the weak people who his right was under attack. It's also give thc weak a strong ideological weapon facing its tyrant. ln l